Hubungan Kesadaran Interoseptif Dengan Kesadaran Hipoglikemia pada Penderita DM Tipe 2 - Maria Manungkalit; Ni Putu Wulan P. Sari; Agustina Ch. Bura Mare (Universitas Malahayati, 2026)
ABSTRACT One condition frequently experienced by people with type 2 diabetes is hypoglycemia, which can drastically lower blood glucose levels. Undetected and untreated hypoglycemia can lead to serious complications, including seizures or loss of consciousness. However, many people with type 2 diabetes have difficulty recognizing the symptoms of hypoglycemia in its early stages. One factor thought to influence the ability to detect hypoglycemia symptoms is interoceptive awareness, which is a person's ability to perceive and identify internal bodily sensations, such as heartbeat, breathing, and changes in blood glucose levels. The purpose of this study was to explain the relationship between interoceptive awareness and hypoglycemia awareness in people with type 2 diabetes. This study used a cross-sectional design. The population comprised all 173 people with type 2 diabetes in the Mulyorejo Community Health Center (Puskesmas) in Surabaya in June 2025. A total of 110 people met the sample criteria. The instrument used to measure interoceptive awareness was the Multidimensional Assessment of Interoceptive Awareness–Version 2 (MAIA-2) questionnaire, and the HypoA-Q questionnaire was used for hypoglycemia awareness. Hypoglycemia awareness was low despite adequate interoceptive awareness. There was no relationship between interoceptive awareness and glycemia awareness in patients with type 2 diabetes. Nteroceptive awareness (the ability to perceive general body signals) is not always associated with hypoglycemia awareness due to different biological mechanisms and neurological adaptations. Keywords : Hypoglycemia Awareness, Interoceptive Awareness, Type 2 Diabetes Mellitus. ABSTRAK Salah satu kondisi yang sering dialami oleh penderita DM tipe 2 adalah hipoglikemia, yang dapat menurunkan kadar glukosa darah secara drastis. Hipoglikemia yang tidak terdeteksi dan tidak ditangani dengan cepat dapat menyebabkan komplikasi serius, termasuk kejang atau kehilangan kesadaran. Namun, banyak penderita DM tipe 2 yang kesulitan mengenali gejala hipoglikemia pada tahap awal. Salah satu faktor yang diduga mempengaruhi kemampuan deteksi gejala hipoglikemia adalah kesadaran interoseptif, yaitu kemampuan seseorang untuk merasakan dan mengidentifikasi sensasi tubuh internal, seperti detak jantung, pernapasan, dan perubahan kadar glukosa darah.Tujuan penelitian ini adalah untuk menjelaskan hubungan kesadaran interoseptif dengan kesadaran hipoglikemia pada penderita DM tipe 2. Penelitian ini menggunakan desain cross-sectional dengan jumlah populasi adalah seluruh penderita DM tipe 2 di wilayah kerja Puskemas Mulyorejo Surabaya pada bulan Juni 2025 sebanyak 173 orang. jumlah sampel yang memenuhi kriteria sebanyak 110 orang. Instrumen yang digunakan untuk variabel kesadaran interoseptif adalah kuesioner Multidimensional Assessment of Interoceptive Awareness–Version 2 (MAIA-2) dan variable kesadaran hipoglikemia menggunakan kuesioner HypoA-Q. Kesadaran hipoglikemianya rendah walaupun kesadaran interoseptifnya cukup. Tidak terdapat hubungan antara kesadaran interoseptif dengan kesadaran glikemia pada penderita DM tipe 2. Kesadaran interoseptif (kemampuan merasakan sinyal tubuh secara umum) tidak selalu berhubungan dengan kesadaran hipoglikemia karena adanya mekanisme biologis dan adaptasi neurologis yang berbeda. Kata Kunci: Kesadaran Interoseptif, Kesadaran Hipoglikemia, Diabetes Melitus Tipe 2.